Structural insights into biased signaling at chemokine receptor CCR7 - Kotaro Tanaka; Kouki Nishikawa; Yuki Shiimura; Yoshinori Fujiyoshi; Naotaka Tsutsumi (Proceedings of the National Academy of Sciences, 2026)
CC chemokine receptor 7 (CCR7), which orchestrates adaptive immunity, exhibits a phenomenon known as biased agonism. CCL19 induces robust G-protein signaling and β-arrestin recruitment, leading to transient signaling. In contrast, CCL21 preferentially activates G-protein pathways with minimal arrestin engagement, resulting in sustained signaling and differential functional outcomes. Here, we present the cryo-EM structures of the human CCR7–G i complex with either CCL19 or CCL21. The structures reveal that while both engage a conserved orthosteric pocket, they adopt markedly distinct binding poses. Notably, the compact 30s loop of CCL21 inserts deeply into the receptor’s extracellular vestibule, whereas the corresponding loop of CCL19 rests atop extracellular loop 2. Molecular dynamics simulations further reveal that these distinct binding modes induce differential intracellular dynamics, linked to the rotameric state of Y83 at the intracellular end of transmembrane helix 1. We demonstrate that CCL19 stabilizes a flexible conformational ensemble with a highly dynamic helix 8, creating a lateral opening favorable for GPCR kinase engagement. Conversely, CCL21 restricts this flexibility, locking the receptor in a state that precludes kinase interaction while maintaining G-protein coupling. Corroborated by functional data, these findings provide key insights into the structural basis of biased agonism at CCR7 and establish a foundation for rational design of pathway-selective immunomodulators.